Singapore : A Case Study in Rapid Development - Bercuson, Kenneth (Washington, D.C. : International Monetary Fund, 1995)
Since attaining independence in 1965, Singapore has experienced exceptionally rapid growth, low inflation, and a healthy balance of payments. This paper reviews Singapore's economic development from a long-term perspective and examines some of the factors that have contributed to the rapid growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet